Logging of rainforest and conversion to oil palm reduces bioturbator diversity but not levels of bioturbation - Tuma, J; Fleiss, S; Eggleton, P; Frouz, J; Klimes, P; Lewis, O; Yusah, K; Fayle, T (Elsevier, 2019)
Anthropogenic habitat change is a major driver of species extinctions and altered species communities worldwide. These changes are particularly rapid in the tropics, where logging of rainforests and conversion to agricultural habitats is widespread. Because species have varying effects on their abiotic environment, we expect shifts in species composition to drive changes in ecosystem processes. One important ecosystem process is animal-driven bioturbation: the turnover of soil material by soil-dwelling organisms. We developed a protocol for measuring aboveground bioturbation, and assessed how bioturbation rates and standing amounts of aboveground bioturbated soil change as primary tropical rainforests are logged and converted to oil palm plantation. By identifying the animals that created soil structures, we assigned bioturbation activity to different soil-dwelling groups. Across all habitats, most standing bioturbated soil was generated by termites (97.0%), while short-term, small-scale bioturbation was mainly generated by earthworms (87.3%). The species diversity of social insects (ants and termites) involved in bioturbation was higher in primary forest than in either logged forest or oil palm plantation. However, neither standing bioturbated soil, nor short-term bioturbation rate differed among habitats. Unexpectedly, in primary forest, high levels of bioturbation were associated with low bioturbator diversity. This was because two termite species, where present, conducted nearly all bioturbation. There was no relationship between levels of bioturbation and diversity in the other habitats. Our results emphasize the importance, across all habitats, of termites for generating standing aboveground soil structures, and earthworms for short-term soil turnover. In oil palm plantation, bioturbation relies on a smaller number of species, raising concerns about future environmental change and consequent species loss.